Gastos públicos municipais e crescimento econômico: uma análise dos municípios maranhenses de 2003 a 2014 - FRANÇA, Patrícia Reis (2018)
This paper aims to explain the theme of municipal public spending and its relationship with economic growth, based on a review of the international and national literature on the subject and culminating in an analysis of data from the counties of the State of Maranhão. Knowing that several variables can contribute to the growth of an economy, this paper does not intend to explain all the economic performance of the counties through public spending, but to verify in a specific way how this aspect operates. For this analysis, consider the expenses related to the so-called social infrastructure, such as Education, Health, Basic Sanitation and Urbanism and Housing. Therefore, these are the variables that compose the econometric model explored in the paper, in order to examine how they influence the economic growth of the counties of Maranhão. To perform this analysis, data from the 217 counties of the State were used in the period from 2003 to 2014. These data were taken from the Instituto Brasileiro de Geografia e Estatística (IBGE) and Secretaria do Tesouro Nacional (FINBRA/STN). To execute the econometric model, the Ordinary Least Squares (OLS) method was used, by Eviews software as a tool. The results point to a greater significance of the public investments in Education, corroborating with the literature that indicates the human capital as an important motivator of growth, increasing the productivity and the income per capita. On the other hand, it should be noted that the participation of the federal and state public sectors reduced the role of the municipal sphere in expenses such as Basic Sanitation and Urbanism and Housing, with repercussions on the results achieved.